2020
DOI: 10.1080/12298093.2020.1784592
|View full text |Cite
|
Sign up to set email alerts
|

A New Report on Edible Tropical Bolete,Phlebopus spongiosusin Thailand and Its Fruiting Body Formation without the Need for a Host Plant

Abstract: Phlebopus spongiosus is a well-known edible ectomycorrhizal mushroom indigenous to southern Vietnam. The mushroom specimens collected from northern Thailand in this study were identified as P. spongiosus. This identification was based on morphological characteristics and the multi-gene phylogenetic analyses. Pure cultures were isolated and the relevant suitable mycelial growth conditions were investigated. The results indicated that the fungal mycelia grew well on L-modified Melin-Norkans, and Murashige and Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Sanmee et al (2010) found that P. portentosus mycelia grew well on modified Gamborg, modified Melin Norkans and MS media at 30 o C and pH 4. Kumla et al (2020) found that P. spongiosus mycelia grew well on L-modified Melin-Norkans and Murashige and Skoog agar at 30 o C at an initial pH of 5. Siri-in et al (2014) studied the growth conditions of pure Scleroderma sinnamariense mycelia.…”
Section: Discussionmentioning
confidence: 98%
“…Sanmee et al (2010) found that P. portentosus mycelia grew well on modified Gamborg, modified Melin Norkans and MS media at 30 o C and pH 4. Kumla et al (2020) found that P. spongiosus mycelia grew well on L-modified Melin-Norkans and Murashige and Skoog agar at 30 o C at an initial pH of 5. Siri-in et al (2014) studied the growth conditions of pure Scleroderma sinnamariense mycelia.…”
Section: Discussionmentioning
confidence: 98%
“…Sanmee et al (2010) found that P. portentosus mycelia grew well on modified Gamborg, modified Melin Norkans and MS media at 30 o C and pH 4. Kumla et al (2020) found that P. spongiosus mycelia grew well on L-modified Melin-Norkans and Murashige and Skoog agar at 30 o C at an initial pH of 5. Siri-in et al (2014) studied the growth conditions of pure Scleroderma sinnamariense mycelia.…”
Section: Molecular Identificationmentioning
confidence: 98%
“…Finally, a gold coating was applied before observations were conducted using the JSM IT 200 SEM system manufactured by JEOL in Tokyo, Japan. Morphological identification was based on several references, including Boedjin (1951), Kumla et al (2012), Pham et al (2012), Kumla et al (2020), and Baroni et al (2015).…”
Section: Morphological Identificationmentioning
confidence: 99%
“…eaten mushroom in China and Thailand due to its high nutrient content and popularity in the local market (Ji et al 2011;Kumla et al 2012;Kumla et al 2020). In addition, this species holds the distinction of being the initial species within the Boletaceae order to undergo large-scale industrial cultivation (Ji et al 2011;Kumla et al 2015).…”
mentioning
confidence: 99%